Attenuation of the Hepatoprotective Effects of Ileal Apical Sodium Dependent Bile Acid Transporter (ASBT) Inhibition in Choline-Deficient L-Amino Acid-Defined (CDAA) Diet-Fed Mice - Rao, Anuradha; Peppel, Ivo P. van de; Gumber, Sanjeev; Karpen, Saul J.; Dawson, Paul A. (Frontiers in Medicine, 2020)
Non-alcoholic fatty liver disease (NAFLD) is a major growing worldwide health problem. We previously reported that interruption of the enterohepatic circulation of bile acids using a non-absorbable apical sodium-dependent bile acid transporter inhibitor (ASBTi; SC-435) reduced the development of NAFLD in high fat diet fed mice. However, the ability of ASBTi treatment to impact the progression of NAFLD to non-alcoholic steatohepatitis (NASH) and fibrosis in a diet-induced mouse model remains untested. In the current study, we assessed whether ASBTi treatment is hepatoprotective in the choline-deficient, L-amino acid-defined (CDAA) diet model of NASH-induced fibrosis. Methods: Male C57Bl/6 mice were fed with: A) choline-sufficient L-amino acid-defined diet (CSAA) (31 kcal% fat), B) CSAA diet plus ASBTi (SC-435; 60 ppm), C) CDAA diet, or D) CDAA diet plus ASBTi. Body weight and food intake were monitored. After 22 weeks on diet, liver histology, cholesterol and triglyceride levels, and gene expression were measured. Fecal bile acid and fat excretion were measured, and intestinal fat absorption was determined using the sucrose polybehenate method. Results: ASBTi treatment reduced bodyweight gain in mice fed either the CSAA or CDAA diet, and prevented the increase in liver to body weight ratio observed in CDAA-fed mice. ASBTi significantly reduced hepatic total cholesterol levels in both CSAA and CDAA-fed mice. ASBTi-associated significant reductions in hepatic triglyceride levels and histological scoring for NAFLD activity were observed in CSAA but not CDAA-fed mice. These changes correlated with measurements of intestinal fat absorption, which was significantly reduced in ASBTi-treated mice fed the CSAA (85% vs 94%, P < 0.001) but not CDAA diet (93% vs 93%). As scored by Ishak staging of Sirius red stained liver sections, no hepatic fibrosis was evident in the CSAA diet mice. The CDAA diet-fed mice developed hepatic fibrosis, which was increased by the ASBTi. Conclusions: ASBT inhibition reduced intestinal fat absorption, bodyweight gain and hepatic steatosis in CSAA diet-fed mice. The effects of the ASBTi on steatosis and fat absorption were attenuated in the context of dietary choline-deficiency. Inhibition of intestinal absorption of fatty acids may be involved in the therapeutic effects of ASBTi treatment.